2021
DOI: 10.3389/fonc.2020.604084
|View full text |Cite
|
Sign up to set email alerts
|

Driving Immune Responses in the Ovarian Tumor Microenvironment

Abstract: Ovarian cancer is the leading cause of death among gynecological neoplasms, with an estimated 14,000 deaths in 2019. First-line treatment options center around a taxane and platinum-based chemotherapy regimen. However, many patients often have recurrence due to late stage diagnoses and acquired chemo-resistance. Recent approvals for bevacizumab and poly (ADP-ribose) polymerase inhibitors have improved treatment options but effective treatments are still limited in the recurrent setting. Immunotherapy has seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 147 publications
0
22
0
Order By: Relevance
“…The TME has an essential role in suppressing or enhancing the immune response (6). Recent studies have shown that an immunosuppressive TME is a major obstacle to successful implementation of tumor immunotherapy in OC patients (7,8). Therefore, understanding how the immune microenvironment of OC may hinder effective immune attack could guide the prediction of OC patients and promote more practical applications of immunotherapy in OC.…”
Section: Introductionmentioning
confidence: 99%
“…The TME has an essential role in suppressing or enhancing the immune response (6). Recent studies have shown that an immunosuppressive TME is a major obstacle to successful implementation of tumor immunotherapy in OC patients (7,8). Therefore, understanding how the immune microenvironment of OC may hinder effective immune attack could guide the prediction of OC patients and promote more practical applications of immunotherapy in OC.…”
Section: Introductionmentioning
confidence: 99%
“…However, limited benefits have emerged in OC, even leading to premature termination due to the futility of some studies. Different components of the OC tumor microenvironment (TME) contribute to this failure, such as myeloid-derived suppressor cells (MDSCs), tumor-associated macrophages (TAMs), T-cells, cytokines, and soluble factors [37][38][39][40]. MDSCs exert immunosuppressive functions, such as the inhibition of T-effector and natural killer (NK)-cells, and are induced under proinflammatory cytokines, IFNγ, tumor necrosis factor-alpha (TNFα), interleukin (IL)-6 [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, limited benefits have emerged in the OC, even leading to the premature termination for the futility of some studies. Different components of the OC tumor microenvironment (TME) contribute to this failure, such as myeloid-derived suppressor cells (MDSCs), tumorassociated macrophages (TAMs), T-cells, cytokines, and soluble factors [37][38][39][40]. MDSCs exert immunosuppressive functions, such as the inhibition of T-effector and natural killer (NK)-cells, and are induced under pro-inflammatory cytokines, IFNγ, tumor necrosis factor-alpha (TNFα), interleukin (IL)-6 [41].…”
Section: Discussionmentioning
confidence: 99%